Accurate measurement of JHH in overlapped signals by a TOCSY‐edited SERF Experiment. (20th February 2017) - Fredi, André; Nolis, Pau; Parella, Teodor
Abstract : Selective refocusing (GSERF or the recent PSYCHEDELIC) experiments were originally designed to determine all proton–proton coupling constants ( J HH ) for a selected proton resonance. They work for isolated signals on which selective excitation can be successfully applied but, as it happens in other selective experiments, fail for overlapped signals. To circumvent this limitation, a doubly‐selective TOCSY‐GSERF scheme is presented for the measurement of J HH in protons resonating in crowded regions. This new experiment takes advantage of the editing features of an initial TOCSY transfer to uncover hidden resonances that become accessible to perform the subsequent frequency‐selective refocusing. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : A doubly‐selective TOCSY‐GSERF scheme is presented for the measurement of J HH in protons resonating in crowded regions. This new experiment takes advantage of the editing features of an initial TOCSY transfer to uncover hidden resonances that become accessible to perform the subsequent frequency‐selective refocusing.